Modeling and Implementation of a Hybrid Solar-Wind Renewable Energy System for Constant Power Supply - Mubeezi, Conceptar; Umaru, Kalyankolo; Eze, Val Hyginus Udoka; Jim, Migisha; Asikuru, Salama; Musa, Nassaga; Ochima, Noah; Okafor, Wisdom (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
In recent years, Uganda has significantly increased the use of renewable energy sources, particularly solar and wind power. These energy sources are especially crucial in rural and remote areas where connecting to the national grid is challenging. Renewable Energy Sources (RES) have proven to be cost-effective alternatives to traditional energy sources, which often require substantial investments in transmission and distribution networks. This study focuses on designing and implementing a hybrid renewable energy system that integrates both solar and wind power. The research successfully established a reliable and continuous power supply for the community through the combination of wind and solar energy. The hybrid power generation system operates by simultaneously monitoring solar and wind energy using an ACS712 current and voltage sensor. Controlled by a microcontroller, the system employs dual-channel relay switches to activate the power source with sufficient energy to charge the battery. The programming for this system was conducted using C++ and Arduino software. This study highlights the vast potential within the field of sustainable energy. With rapid and economical electricity production, this hybrid system paves the way toward a greener future, where our energy needs can be met in an environmentally friendly manner.